2002
DOI: 10.1002/jez.10051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genic substitution at the pink‐eyed dilution locus on the proliferation and differentiation of mouse epidermal melanocytes in vivo and in vitro

Abstract: Cells positive to the dopa reaction (melanocytes) as well as to the combined dopa-premelanin reaction (melanoblasts and melanocytes) in the epidermis of C57BL/10JHir-p/p (pink-eyed dilution) mice were fewer and less reactive than in C57BL/10JHir (black, P/P) mice, suggesting that the proliferation and differentiation of p/p melanocytes are inhibited. To confirm the inhibitory effects of p gene on the proliferation and differentiation of epidermal melanocytes, we cultured epidermal cell suspensions of neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…17 The eumelanin content, the proliferation, and the differentiation of melanoblasts and melanocytes are all greatly reduced p mutant mice. 17 It therefore seems quite reasonable to assume that the quantity and/or quality of melanin, that determines part of the risk of skin cancer, is strongly influenced by the OCA2 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The eumelanin content, the proliferation, and the differentiation of melanoblasts and melanocytes are all greatly reduced p mutant mice. 17 It therefore seems quite reasonable to assume that the quantity and/or quality of melanin, that determines part of the risk of skin cancer, is strongly influenced by the OCA2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…17 The eumelanin content, the proliferation, and the differentiation of melanoblasts and melanocytes are all greatly reduced p mutant mice. 17 It therefore seems quite reasonable to assume that the quantity and/or quality of melanin, that determines part of the risk of skin cancer, is strongly influenced by the OCA2 protein. In fact, a decrease of eumelanin in OCA2-variant melanocytes could contribute to mutagenesis and confer susceptibility to MM and nonmelanoma skin cancer by enhancing toxicity of free radicals following ultraviolet exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The OCA2 gene maps to chromosome 15q11.2-q12, is highly polymorphic [Lee et al, 1995], and encodes an 838-amino acid melanosomal protein resembling a channel or a transporter [Gardner et al, 1992;Ramsay et al, 1992;Rinchik et al, 1993;Rosemblat et al, 1998;Staleva et al, 2002]. OCA2 plays an important role in controlling the eumelanin content of melanocytes [Hirobe et al, 2002;Lamoreux et al, 1995;Orlow and Brilliant, 1999;Ozeki et al, 1995;Tamate et al, 1989] via the processing of tyrosinase and the regulation of the melanosomal pH [Chen et al, 2002;Toyofuku et al, 2002]. It has recently been shown that three OCA2 intronic variants (rs7495174, rs4778241, and rs4778138) were closely associated with normal phenotypic variations in human eye color [Duffy et al, 2007].…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the reduction in the amount of eumelanin deposited (12, 13), melanin granules within the hair shafts of p/p mice are smaller than those in P/P mice (14). The p/p melanocytes contain smaller and rounder (15, 16) immature (17–19) melanosomes, and the number of stage III and IV melanosomes are much fewer than in P/P melanocytes (20–22). Levels of tyrosinase, the rate‐limiting enzyme in melanin synthesis, are decreased in melanocytes of p/p mice (23–26).…”
Section: Introductionmentioning
confidence: 99%